(untitled) (Journal of Economic Additions, 2025)
This paper examines the rapid adoption of digital strategies in university education and management, viewing digital transformation as a strategic path for higher education. It explores dimensions of digital transformation, features of fourth-generation universities, and indicators of digital readiness and identity. Using a descriptive–analytical approach, the study reviews relevant literature and the initiatives of Algeria’s Ministry of Higher Education. Findings emphasize the need for a roadmap to guide digital transformation, highlighting universities’ central role as drivers of change, innovation, and progress in the sector. Jel Classification Codes: O33, I23, I28